GERAKAN 30 SEPTEMBER 1965 DALAM PERSPEKTIF FILSAFAT SEJARAH MARXISME - Permata, Harsa (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2015)
The Thirtieth of September Movement 1965 (G30S 1965), is a movement which is very influential in the history of Indonesian society until today. After G30S 1965, freedom of ideology began to be restricted in Indonesia. In addition, the slaughter of millions of human beings, with the reason to eradicate communism, began to take place after G30S 1965. A restriction on freedom of ideology is also touching the academic life. Based on TAP MPRS No.. XXV/1966, the study of Marxism-Leninism ideology is limited. This resulted in the lack of alternative and scientific thought in the academic world in Indonesia. The Thirtieth of September Movement 1965 (G30S 1965), is the manifestation of class contradictions in the Indonesian capitalist society. G30S 1965, emphasize the class contradictions in Indonesian society. Social classes in Indonesian society is a military bourgeoisie represented by the TNI (Indonesian Armed Forces), the proletariat, as represented by the PKI (Indonesian Communist Party). President Sukarno, was the one who stand in the middle of the contradiction between the army and the PKI. And then, G30S 1965, used as an excuse by Suharto and the army to stage a creeping coup against President Sukarno and slaughtered millions of cadres and sympathizers of the PKI. After the G30S 1965, the New Order regime of Suharto opened the door wide open for international capitalism to exploit the natural resources of Indonesia. Suharto's New Order regime improves Indonesian capitalism.